The effects of firm's risk, independent directors and audit committees on income increasing and income decreasing earnings management - Abdul Rahman, Rashidah; Wan Mohamad, Masliza; Nik Salleh, Nik Mohamad Zaki (2011)
This study examines the association between board characteristics, ethnicity and the level of risks and its effect on discretionary accruals as a proxy of earnings management. The sample of the study comprises of 298 randomly sampled firms over the year 2004 to 2009. The 6 year period of the study covers the revised code of corporate governance in 2007 which requires independent directors to be at least financially literate, possessed qualification and be a member of professional accounting bodies. Contrary to the commonly-held belief that highly-qualified and experienced directors effectively act as deterrent to earnings management, the results revealed that higher earnings management is associated with more qualified and experienced directors measured by independent directors qualification and CEO tenure. However an independent director who is a member of professional accounting is negatively associated to earnings management. A new finding of this study is the importance of chairman independence. The result revealed that chairman independence is more effective in reducing earnings management in comparison to independent directors. Issue on ethnicity is equally interesting as earnings management is observed to be lower when there is greater ethnic diversity in the composition of board members and ethnic-wise, appears nominally balanced in the number of representatives. Malaysian manufacturing firms, predominantly owned by the Chinese entrepreneur, may therefore potentially reduce agency conflicts and earnings management by muting its partiality to own ethnic when appointing board members, broadening instead its acceptance to other ethnic backgrounds. However, the findings of this study also indicate a positive association between Malay directors and earnings management necessitating a fUl1her study on the factors that may have attributed to the scenario. One possible explanation is that the existence of Malay directors is merely in fulfilling the KLSE requirement rather than executing the monitoring tasks of the board of directors.